Search for invisible decays of a Higgs boson using vector-boson fusion in pp collisions at √s = 8 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Davygora, Yuriy; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (Journal of high energy physics, 2016)
A search for a Higgs boson produced via vector-boson fusion and decaying into invisible particles is presented, using 20.3 fb−1 of proton-proton collision data at a centre-of-mass energy of 8 TeV recorded by the ATLAS detector at the LHC. For a Higgs boson with a mass of 125 GeV, assuming the Standard Model production cross section, an upper bound of 0.28 is set on the branching fraction of H → invisible at 95% confidence level, where the expected upper limit is 0.31. The results are interpreted in models of Higgs-portal dark matter where the branching fraction limit is converted into upper bounds on the dark-matter-nucleon scattering cross section as a function of the dark-matter particle mass, and compared to results from the direct dark-matter detection experiments.
*The ATLAS collaboration: G. Aad, C.F. Anders, V. Andrei, A.E. Baas, O. Brandt, Y. Davygora, J.I. Djuvsland, M. Dunford, M.P. Geisler, M. Giulini, P. Hanke. J. Jongmanns, E.-E. Kluge, M. Kretz, A. Kugel, V.S. Lang, M. Lisovyi, K. Meier, H. Meyer zu Theenhausen, D.I. Narrias Villar, M. Sahinsoy, S. Schaetzel, V. Scharf, S. Schmitt, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, P. Starovoitov, M. Wessels [und sehr viele weitere Personen]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 29.06.2020